2020
DOI: 10.1002/saj2.20114
|View full text |Cite
|
Sign up to set email alerts
|

Gas diffusion characteristics of agricultural soils from South Greenland

Abstract: The Arctic is warming at twice the global average, which may impact agricultural production in Greenland. Therefore knowledge of the functional properties of Greenlandic soil resources is necessary. The relative soil gas diffusivity [the soil gas diffusion coefficient (D p)-free-air diffusion coefficient (D o) ratio] is the chief parameter controlling gas transport in soils. Predictions of D p /D o are needed to estimate root zone aeration and terrestrial greenhouse gas fluxes. We used existing models to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 58 publications
3
12
2
Order By: Relevance
“…The sensitivity of ε to changes in ρ b of the arctic pasture soils was generally lower (Figure 7c) compared to the temperate cultivated soils, although the low Ω-values pointed toward a lack of soil structure. Weber et al (2020) investigated the pore-network connectivity of the herein presented arctic pasture soils and concluded that the pasture soils showed only little to no soil-structure development, which is in accordance with the low Ω-values found in this study.…”
Section: Dual Fingerprintsupporting
confidence: 87%
See 1 more Smart Citation
“…The sensitivity of ε to changes in ρ b of the arctic pasture soils was generally lower (Figure 7c) compared to the temperate cultivated soils, although the low Ω-values pointed toward a lack of soil structure. Weber et al (2020) investigated the pore-network connectivity of the herein presented arctic pasture soils and concluded that the pasture soils showed only little to no soil-structure development, which is in accordance with the low Ω-values found in this study.…”
Section: Dual Fingerprintsupporting
confidence: 87%
“…The Greenlandic sites are described in Weber et al (2020) and Pesch et al (2020). In total, 396 individual soil core samples from five pasture fields from south-west Greenland were included in this study (132 individual sampling points, three replicates per point).…”
Section: Soils and Soil Samplingmentioning
confidence: 99%
“…The South Greenlandic soils are characterized by a relatively coarse texture and moderate to high organic matter (OM) content and show little to moderate soil development (Jakobsen, 1991); Caviezel et al, 2017;Weber et al, 2020;Pesch et al, 2021). In a recent study, Weber et al (2021) revealed the hydrophobic tendency of Greenlandic agricultural soils, which was attributed to the combination of coarse soil texture and high OM content.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Weber et al (2021) revealed the hydrophobic tendency of Greenlandic agricultural soils, which was attributed to the combination of coarse soil texture and high OM content. Furthermore, Pesch et al (2021) revealed the quasi absence of any soil aggregation and Weber et al (2020) pointed out the complexity of adequate soil aeration because of pronounced pore network tortuosity. The cold environment, relatively coarse soil texture, and the lack of soil development result in large amounts of noncomplexed OM (Pesch et al, 2020), which will be prone to degradation following increasing temperatures (Kirschbaum, 1995) or changes in soil management (Besnard et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation